Effects of the COVID 19 pandemic on the mental health of professional soccer teams: epidemiological factors associated with state and trait anxiety - Santana Esteves, N.; Andarade de Brito, M.; Sobarzo Soto, D. A.; Teixeira Müller, V.; Aedo-Munoz, E.; Brito, C. J.; Miarka, B. (Journal of Physical Education and Sport, 2020)
This study aims to verify associated factors with trait and state anxiety in professional soccer teams during the COVID-19 epidemic. The sample was composed of 529 athletes, coaches, and professional soccer teams' physical trainers during the COVID-19 epidemic. From this amount, 214 were classified with trait-anxiety, and 315 were classified with state-anxiety using the State-Trait Anxiety Inventory (STAI). This study is an epidemiological and cross-sectional study. We applied an observational method, and we performed a remote measurement. The measurement was made via online questionnaires in male and female individuals working on soccer teams (soccer professionals or athletes) who could be affected by anxiety during social isolation in the COVID-19 epidemic. Each questionnaire was composed of sociodemographic questions, self-perceived performance, and State-Trait Anxiety Inventory (STAI). Descriptive data are presented as percentage/absolute frequency. Factor analysis was used to reduce many variables into fewer factors of each anxiety group (state and trait) to verify which variables are associated with the COVID-19 pandemic anxiety state, p=.05. Factor analysis of the trait anxiety group indicated a significant correlation (p= 0001). The trait anxiety group's components correlated 0.43 and 0.84, while the state anxiety demonstrated a correlation between 0.52 and 0.996. The present results highlight the importance of cognitive behavior therapy for professional soccer teams. Its core is cognitive restructuring using the ABC model (antecedents-behavior-consequences). Mental errors and maladaptive behaviors are identified and worked upon considering sociodemographic factors such as gender and schooling levels.